Nuclear myosin is ubiquitously expressed and evolutionary conserved in vertebrates - Kahle, M; Pridalová, J; Spacek, M; Dzijak, R; Hozák, P (Histochemistry and cell biology, 2007)
Nuclear myosin I (NMI) is a single-headed member of myosin superfamily localized in the cell nucleus which participates along with nuclear actin in transcription and chromatin remodeling. We demonstrate that NMI is present in cell nuclei of all mouse tissues examined except for cells in terminal stages of spermiogenesis. Quantitative PCR and western blots demonstrate that the expression of NMI in tissues varies with the highest levels in the lungs. The expression of NMI is lower in serum-starved cells and it increases after serum stimulation. The lifespan of NMI is longer than 16 h as determined by cycloheximide translation block. A homologous protein is expressed in human, chicken, Xenopus, and zebrafish as shown by RACE analysis. The analysis of genomic sequences indicates that almost identical homologous NMI genes are expressed in mammals, and similar NMI genes in vertebrates.
Keywords: Cell Line; Sequence Homology, Nucleic Acid; buněčné jádro; sérum; sekvence aminokyselin; myosin typu I; mužské pohlaví; Mice; Serum; Transcription, Genetic; Myosin Type I; genetická transkripce; konzervovaná sekvence; Cell Nucleus; obratlovci; ženské pohlaví; Gene Expression; zvířata; Humans; Vertebrates; Amino Acid Sequence; fylogeneze; myši; sekvenční homologie nukleových kyselin; exprese genu; buněčné linie; Nucleic Acid Amplification Techniques; Female; techniky amplifikace nukleových kyselin; Conserved Sequence; Phylogeny; lidé; Male; Animals